Expressivity and Musical Shape in Turntablism: Response to Greasley and Prior - Hansen, Kjetil Falkenberg (Empirical Musicology Review, 2013)
This commentary to Greasley and Prior’s paper “Mixtapes and turntablism: DJs’ perspective on musical shape” extends the findings of the study by looking at the turntablism perspective. First, a general discussion on the study’s method and background is given. Then, the role of turntables as musical instruments in creating musical shape is outlined. Finally, some relationships between turntablism techniques, expressive performances and musical shape are presented. In general, the findings in the study support previously published studies in this insufficiently researched area.